2008
DOI: 10.1007/s10038-008-0281-3
|View full text |Cite
|
Sign up to set email alerts
|

Early modification of sickle cell disease clinical course by UDP-glucuronosyltransferase 1A1 gene promoter polymorphism

Abstract: Elevated erythrocyte destruction in sickle cell disease (SCD) results in chronic hyperbilirubinaemia and, in a subset of patients, cholelithiasis occurs. We investigated whether the (TA) n promoter polymorphism in the UDP-glucuronosyltransferase 1A1 gene (UGT1A1) may modify bilirubin metabolism, influencing bilirubinaemia, predisposition to cholelithiasis and subsequent cholecystectomy, in a group of 153 young SCD patients (mean age 12.0 ± 9.0 years) predominantly of Bantu beta S haplotype. The concomitant eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 17 publications
1
10
0
Order By: Relevance
“…Genetic studies of these patients have identified a dinucleotide repeat polymorphism (TA) 5–8 in the TATA box of the UGT1A1 gene promoter that is associated with reduced UGT expression and produces hyperbilirubinemia [30]–[31], [37], [46][47]. This polymorphism has also been observed in small cohorts of sickle cell anemia patients suggesting a common pathogenic link between ethnically divergent etiologies of indirect hyperbilirubinemia [5], [10]–[15], [33]. In the current study, genome-wide genetic screening of a large cohort of sickle cell anemia patients not only confirmed these findings but also supported their biological relevance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Genetic studies of these patients have identified a dinucleotide repeat polymorphism (TA) 5–8 in the TATA box of the UGT1A1 gene promoter that is associated with reduced UGT expression and produces hyperbilirubinemia [30]–[31], [37], [46][47]. This polymorphism has also been observed in small cohorts of sickle cell anemia patients suggesting a common pathogenic link between ethnically divergent etiologies of indirect hyperbilirubinemia [5], [10]–[15], [33]. In the current study, genome-wide genetic screening of a large cohort of sickle cell anemia patients not only confirmed these findings but also supported their biological relevance.…”
Section: Discussionmentioning
confidence: 99%
“…However, sequencing of UGT1A1 has been undertaken in SCD cohorts in Guadeloupe, Portugal, Jamaica, India and the United States; genotyping of 324 SCD children from the Cooperative Study of Sickle Cell Disease (CSSCD) revealed that the common (TA)6 and (TA)7 alleles were present in 75% [10]–[15]. The (TA)7/(TA)7 genotype was associated with increased serum bilirubin levels and cholelithiasis risk compared with the (TA)6/(TA)7 and (TA)6/(TA)6 genotypes across cohorts with suggestions that those with a (TA)8 allele are at highest risk, suggesting a similar pattern of inheritance as observed in Caucasians [10]–[15]. Treatment with hydroxyurea, known to decrease the hemolytic rate in sickle cell anemia patients, was unable to decrease bilirubin levels to normal levels in those with the (TA)7/(TA)7 genotype suggesting that this genetic defect may represent a new pharmacologic target for these patients [14].…”
Section: Introductionmentioning
confidence: 99%
“…Our data showed that the frequency of cholelithiasis was not affected by -α 3.7 deletion. In line with these results, two studies found a similar prevalence of cholelithiasis between SCD patients with and without -α 3.7 deletion [10,12]. In contrast, Vasavda et al [11] observed a reduced risk of cholelithiasis in the positive α-thal patients.…”
Section: Discussionmentioning
confidence: 65%
“…Nevertheless, the role of α-thalassaemia in bilirubin levels and cholelithiasis is controversial in SCD [8][9][10][11][12][13]. Furthermore, there is a lack of information about complications from cholelithiasis in SCD patients with coinheritance of α-thalassaemia.…”
Section: Introductionmentioning
confidence: 99%
“…In sickle cell patients, the number of TA repetitions has been shown to exert an important influence on serum bilirubin levels [122]. Homozygosity for the 7 alelle has been associated with earlier and increased incidence of gallstones in children, and a higher need for cholecystectomy in adults with symptomatic biliary disease [123][124][125][126][127]. Coinheritance of a-thalassemia decreases hemolysis and, therefore, can decrease bilirubin levels, but data are contradictory in defining whether it is sufficient to compensate for the effect of the 7/7 genotype [128,129].…”
Section: Gallstones and Bilirubin Levelsmentioning
confidence: 99%